REORIENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN PENDEKATAN LIFE SKILLS - Desy Aniqotsunainy (Al-Misbah (Jurnal Islamic Studies), 2019)
Life Skills education as one form of alternative approach that develops the capability of graduated quality. The implementation of Life Skills education is part of school reform. One of them through reorientation of learning is focused on the learning of Islamic religious education in principle to manage the curriculum applicable so that life skills can be grown programmed. In the learning process can be a task or project that is a tool to practice integrating competence and life skills in a form of problem-solving contextual in the material being studied.